(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: Thyroglossal duct cyst (TDC) is considered to be the most common congenital neck swelling in children. But its diagnosis can sometimes be challenging, because of abnormal presentation or associated infection. The aim of the present study is to describe the clinical features, anatomical location and management given to these children in the context of Bangladesh. Methods: This retrospective review of the past 7 years’ (between June 2008 and July 2015) records of all children with a histopathologically confirmed diagnosis of TDC was done at the Department of Pediatric Otolaryngology, Dhaka Shisu Hospital, Sher-e-Bangla Nagar, Dhaka. Thirty patients fulfilled the predefined eligibility criteria and were included in the study. Preoperative evaluation consisted of physical examination with regard to movement of the mass with protrusion of the tongue and ultrasonographic assessment of the mass. All the patients were operated by Sistrunk’s approach and outcome was assessed in terms uneventful cure, infection and recurrence. Result: In the present study the children presented with TDC were on an average 7.1 (range: 3.5 - 11 years) years old and were predominantly girls (60%). Majority of patients belonged to middleclass (70%). Urban and rural representations were almost equal. Half of the patients were diagnosed between 5 - 10 years of age. Majority (80%) of the TDCs were located in infrahyoid region just lateral to the midline, 16.7% were located close to the hyoid bone (juxtahyoid) and 3.3% to the suprahyoid region in the midline. All the 30 cases presented with painless cystic swelling which moved upwards with protrusion of tongue. No signs of infection or associated diseases (myxoedema or thyroglossal fistula) were present. An anechoeic character with absence of fluid level was detected with ultrasono imaging of the mass. Conclusion: Clinical presentation and anatomical location and management were almost same as elsewhere in the world. But in the absence of a complete database including the follow up data, it is not feasible to plan for further improvement of the children with TDC. Ibrahim Cardiac Med J 2014; 4(2): 37-42